Domination on the vertices of labeled graphs - Grunsky, I.; Mikhaylova, I.; Sapunov, S. (Algebra and Discrete Mathematics, 2012)
In this paper we introduce and study a domination relation on vertices of vertex-labeled graphs induced by vertex languages comparison. An effective method of checking this relation is developed. Properties of vertices maximal by this relation are investigated. It is shown that dominating vertices form a connected component of the graph.